Interference of Brassicaceae and Poaceae on Canola Hybrids - SILVA,D.R.O. (2019)
ABSTRACT: The objective of this study was to evaluate the initial competitive ability of canola hybrids against Brassicaceae and Poaceae species in terms of root and shoot resources. Two experiments were conducted in greenhouse, in a completely randomized design with four replications. The treatments consisted of interference conditions by root + shoot interference (root+shoot) and shoot interference (Light); and Brassicaceae and Poaceae weeds competing with hybrid of canola (Hyola 61 and Diamond) with different traits for competitiveness. The plant height, root length, dry matter of shoot and root, number of leaves and leaf area were evaluated. Data were compared using orthogonal contrasts. The turnip and volunteer canola reduced root development of the Hyola 61 in root + shoot interference, and among the Brassicaceas weeds, turnip caused greater losses. Brassicaceas weeds caused largest reductions in Diamond’s hybrid growth compared to Poaceae, mainly under light interference. Brassicaceas and Poaceae weeds cause similar damage to Hyola 61 hybrid, and the injury is higher for root +shoot interference. The black oat induce shoot growth in the Diamond hybrid under shoot interference, while among the Brassicaceae weed species, there were no differences.